Bioarchaeology and Climate Change : A View from South Asian Prehistory - Schug, Gwen Robbins (Book collections on Project MUSE., 2011)
Robbins Schug's biocultural synthesis provides us with a new way of looking at the adaptive, social, and cultural transformations that took place in this region during the first and second millennia B.C. Her work clearly and compellingly usurps the climate change paradigm, demonstrating the complexity of human-environmental transformations. This original and significant contribution to bioarchaeological research and methodology enriches our understanding of both global climate change and South Asian prehistory.